KETIDAKSETARAAN SOSIAL DALAM NOVEL RE: DAN PEREMPUAN KARYA MAMAN SUHERMAN - Apriliani, Rika; Mubarok, Insani Wahyu; Rachmawati, Dian Karina (Fon : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Forms of social inequality can appear in people's lives, for example economic inequality and differences in social class. Social inequality is a complex and growing issue, touching various layers and groups in society, including sex workers. The novels Re: and Perempuan depict various sides of women's lives, including violence, discrimination, and their struggle to achieve justice and dignity which is often overlooked. The story in this novel is interesting to examine in terms of social inequality. The formulation of the problem in this research is how forms of social inequality are depicted in the novel Re: and Perempuan by Maman Suherman. The aim of this research is to analyze and identify forms of social inequality reflected in the novel Re: and Perempuan by Maman Suherman. The theory used is Marxism about social classes. This research uses qualitative methods which are described descriptively. The research data is in the form of excerpts from the novels Re: and Perempuan. The data collection technique was carried out using the reading and note-taking method. The results of this research, the novel Re: and Perempuan found characteristics of social inequality, namely capitalism, exploitation, class inequality, social consciousness. This research can be applied in the world of education to build students' critical awareness of social inequality through literature. In addition, material from this research can be integrated into Indonesian language learning and sociology to instill social values, critical thinking and empathy towards vulnerable groups.